The expansion of intensive marine aquaculture in Turkey: The next‐to‐last commodity frontier? - Irmak Ertör; Miquel Ortega‐Cerdà (Wiley, 2025)
Aquaculture is one of the fastest growing food‐producing sectors, and its share in global seafood production is rising significantly compared with capture fisheries. This transforms seafood production practices while allowing capital to expand to new marine commodity frontiers. Building on the conceptualization of aquaculture as a new frontier for capture fisheries, the article aims to uncover how commodity frontiers expand within the intensive marine aquaculture sector and shape the transformation of seafood production by focusing on its recent growth in Turkey. It analyses this transformation based on 22 in‐depth interviews with key social actors in Turkey, as well as a review of sector and state reports and the relevant legislations of Turkey and the European Union, and argues that the three‐pronged horizontal, vertical, and taxonomic expansion already observed in industrial capture fisheries has similarly taken place in intensive marine aquaculture through the commodity widening, deepening, and marketing strategies employed by aquaculture firms.